2014
DOI: 10.1186/1744-8069-10-29
|View full text |Cite
|
Sign up to set email alerts
|

Role of Spinal P2Y6and P2Y11Receptors in Neuropathic Pain in Rats: Possible Involvement of Glial Cells

Abstract: BackgroundThe participation of spinal P2X receptors in neuropathic pain is well recognized. However, the role of P2Y receptors has been less studied. The purpose of this study was to investigate the contribution of spinal P2Y6,11 receptors following peripheral nerve damage induced by spinal nerve ligation. In addition, we determined the expression of P2Y6,11 receptors in the dorsal spinal cord in presence of the selective P2Y6,11 receptors antagonists. Furthermore, we evaluated the participation of spinal micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 56 publications
3
41
0
Order By: Relevance
“…This inhibitor cocktail contained MRS 2179 (30 mM, P2Y 1 antagonist), AR-C 118925XX (10 mM, P2Y 2 antagonist), MRS 2578 (30 mM, P2Y 6 antagonist), and NF 340 (30 mM, P2Y 11 antagonist). [30][31][32] This combination of P2Y inhibitors blocked eHACSs, but did not alter ''control-like'' events or the overall frequency of spontaneous Ca 2þ signals (Figure 3(d) to (f), n ¼ 13 endfeet from 6 brain slices, N ¼ 5). Interestingly, treatment of SAH brain slices with the phospholipase C inhibitor, U73122 (30 mM, 30 min) abolished both SAH-induced eHACSs and all ''control-like'' events (0.026 AE 0.007 Hz to 0 Hz, n ¼ 5 endfeet from 3 brain slices, N ¼ 3).…”
Section: P2y Receptors Mediate Sah-induced Ehacssmentioning
confidence: 88%
“…This inhibitor cocktail contained MRS 2179 (30 mM, P2Y 1 antagonist), AR-C 118925XX (10 mM, P2Y 2 antagonist), MRS 2578 (30 mM, P2Y 6 antagonist), and NF 340 (30 mM, P2Y 11 antagonist). [30][31][32] This combination of P2Y inhibitors blocked eHACSs, but did not alter ''control-like'' events or the overall frequency of spontaneous Ca 2þ signals (Figure 3(d) to (f), n ¼ 13 endfeet from 6 brain slices, N ¼ 5). Interestingly, treatment of SAH brain slices with the phospholipase C inhibitor, U73122 (30 mM, 30 min) abolished both SAH-induced eHACSs and all ''control-like'' events (0.026 AE 0.007 Hz to 0 Hz, n ¼ 5 endfeet from 3 brain slices, N ¼ 3).…”
Section: P2y Receptors Mediate Sah-induced Ehacssmentioning
confidence: 88%
“…Other antibodies have also been used to examine the existence of the murine P2Y 11 . The P2Y 11 antibody #AB9590 targeting the human P2Y 11 C-terminus detects a large, 75-kDa band on western blot, which is believed to be P2Y 11 on the basis of the results of experiments using rat tissue [41,42], and it has been claimed that another antibody with an unknown epitope confirms P2Y 11 receptor expression in rat neutrophils with a 40-kDa signal [43].…”
Section: P2y 11 Antibodies Lack Specificitymentioning
confidence: 99%
“…It is also worth noting that NF157, NF340, and NF546 have all been used to study the murine BP2Y 11 -like receptort hat shows many of the same properties as seen in humans [14,[41][42][43][82][83][84]. Assuming that no P2Y 11 receptor exists in murines, these compounds must have other mechanisms by which they interfere with cell signalling.…”
Section: Selective P2y 11 Activation and Inhibitionmentioning
confidence: 99%
“…Characteristic features of neuropathic pain are hyperalgesia, allodynia, and spontaneous pain. Numerous pieces of evidence have shown that upregulation of spinal pain mediators and related receptors contributes to neuropathic pain 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%